(3GdQbGHI GdeGdjI Ydi GdfabGJ GdYGeIs - (3EHQGgje (B, (3Hf OGhOs ((3GdbGgQI(B:s (3OGQ GdcJGH GdMOjK(B,s, 2020)
(3jgOa gOG GdcJGH Gdi GHQGR GdeHGOF GdShjI GdJj JMce eGdjI GdOhdI hGdQbGHI YdjgG Ydi GdNUhU, HOAG ef JMUjd GdehGQO Gdi cjajI EfaGbgG aj GdChLg GdeMOOI TQYG(B. (3ef gfG abO YGdL gPG GdcJGH YOOG ef GdJSGDdGJ fLeYgG aj ETcGdjI (B:(3cja JJe QbGHI GdfabGJ GdJj JUQagG GdOhdI Ch EMOi GdgjFGJ GdJGHYI dgG ef efXhQ GdTQjYI GdESdGejI hGdJTQjY GdhVYj? heG GdPj jLSO JMbjb aYGdjJgG? heG GdVhGHW aj Cf JCNO cd fabI eLQGgG GdOj hLgJ Edjg(B. (3hefg Je JfGhd GdehVhY ef NdGd aUdjf CSGSjjf geG (B: (3eSGQ GdfabGJ GdYGeI hChLg GdQbGHI YdjgG, hCfXeI GdQbGHI GdeGdjI Ydi GdfabGJ GdYGeI(B.s
(3GdeQGLY U(B.203s
Keywords: (3GdQbGHI GdeGdjIs; (3GdfabGJ GdYGeIs; (3JObjb GdMSGHGJ GdMchejIs